Factors affecting progression to permanent atrial fibrillation in an unselected population of patients with non-permanent form of atrial fibrillation. (25th November 2020) - Malavasi, V.L; Fantecchi, E; Tordoni, V; Melara, L; Barbieri, A; Valenti, A.C; Menozzi, M; Sgreccia, D; Talarico, M; Imberti, J; Vitolo, M; Boriani, G
Abstract: Background: Natural history of atrial fibrillation (AF) shows a progression of arrhythmia from non-permanent to permanent AF. Permanent AF was found associated with a worse prognosis than non-permanent one. Aim: To assess the factors associated with progression to permanent AF in an unselected population of AF patients with non-permanent AF. Methods: In this prospective study we enrolled in- as well as out-patients with non-permanent AF and age ≥18 years, with at least one episode of ECG-documented AF within 1 year. The patients were followed-up at 1 month and every 6 months thereafter. Results: Out of 523 patients, 314 (60%) were in non-permanent AF (80 [25.5%] paroxysmal AF, 165 [52.5%] persistent AF, 69 [2%] first diagnosed AF), mostly male (188, 59.9%), median age 71 years (IQ range 62–77), median CHA2DS2VASc 3 (1–4), median HATCH score 1 (1–2). After a median follow-up of 701 (IQ range 437–902) days, 66 patients (21%) showed permanent AF. CHA2DS2VASc and HATCH scores were incrementally associated to progression to permanent AF (CHA2DS2VASc χ 2 p=0.001; HATCH χ 2 p=0.017; p for trend CHA2DS2VASc <0.001, HATCH p=0.001). At multivariable Cox proportional hazard regression the following variables were significantly associated with AF progression: age (hazard ratio [HR] 1.041; 95% CI: 1.004–1.079; p=0.028), at least moderate left atrial (LA) enlargement (>42 ml/m 2 ) (HR 2.092; 95% CI: 1.132–3.866; p=0.018), antiarrhythmics drugs after the enrollment (HR 0.087; 95% CI: 0.011–0.662; p=0.018), EHRA score >2 (HR 0.351; 95% CI: 0.158–0.779; p=0.010) and Valvular HD (HR 2.161; 95% CI: 1.057–4.420; p=0.035). Adding LA dilation to HATCH score (HATCH-LA) and assigning 2 points based on multivariable Cox regression, HATCH-LA was statistically better in ROC curves in prediction of AF progression vs HATCH score (area under the curve 0.695 vs 0.636; DeLong p=0.0225). Survival-free curves on freedom from permanent AF using as discriminator HATCH-LA score ≤2 vs >2 led to a statistically significant difference (χ 2 =16.080 p<0.001), but the same was not found for HATCH score (χ 2 =3.099; p=0.078). Conclusions: In patients without permanent AF, progression of AF was independentely related to age, LA dilation, AF symptoms severity, antiarrhythmic drugs and Valvular HD. HATCH score predicted AF progression and adding to it LA dilation (at least moderate) improved patients stratification for the risk of evolution to permanent AF. Funding Acknowledgement: Type of funding source: None